The tourist gaze 3.0 - Urry, John, 1946-2016; Larsen, Jonas, ....- (Los Angeles ; London : SAGE, 2011)
"The original Tourist Gaze was a classic, marking out a new land to study and appreciate. This new edition extends into fresh areas with the same passion and insight of the object. Even more essential reading'"--Nigel Thrift, Vice-Chancellor, Warwick University. "This new edition of a seminal text restructures, reworks and remakes the groundbreaking previous versions so making this very successful book even more relevant for tourism students, researchers and designers in the new century. The tourist gaze remains an agenda setting theory; here it incorporates new principles and research. Packed full of fascinating insights this major new edition is fresh and contemporary, intelligently broadening its theoretical and geographical scope and providing a nuanced account which responds to various critiques. All chapters have been significantly revised to include up-to-date empirical data, many new case studies and fresh concepts. Three new chapters have been added which explore: photography and digitization, embodied performances, risks and alternative futures. Innovative and informative this book is essential reading for all involved in contemporary tourism, leisure, cultural policy, design, economic regeneration, heritage and the arts."--Publisher's description.
Theories -- Mass tourism -- Economies -- Working under the gaze -- Changing tourist cultures -- Places, buildings and design -- Vision and photography -- Performances -- Risks and futures.
Previous edition: 2002.
Includes bibliographical references (pages 241-263) and index.
Keywords: Tourism